El saneamiento por evicción en los contratos de compraventa en el Ecuador - Sampedro Vásconez, Adriana Stefania (2017)
It is an investigation that has tried to know the effects that occur after perfectioning the contract of sale, since when this is done, it is evident that the seller must guarantee to the Buyer the peaceful use of the good, which implies that the buyer must be able to enjoy the good, without any disturbance that prevents it. In order to guarantee this effect, the investigation deepened in the legal and doctrinal context, and was able to deduce that being sanitation a single action that proceeds before the disturbance of the sold goods, there is an under classification: sanitation by eviction and redhibitory vices. Sanitation was studied by eviction, and it was determined that this subdivision operates when the good sold has problems of a legal nature, which causes its buyer a limitation in the domain, through a legal action that arises on the property. Whereas, redhibitory vices arise when the property has physical damage, which prevents its natural use and that the buyer could not determine at the time of purchase. The investigation analyzed both types of sanitation, determining the conditions and requirements that must exist to be able to raise one or another action, in order to ensure the eviction on the contract of sale.